2009
DOI: 10.1590/s0074-02762009000700017
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal activity of Hammada scoparia (Pomel) Iljin leaf extracts and the principal alkaloids isolated from them against Galba truncatula

Abstract: The molluscicidal activity of Hammada scoparia leaf extracts and the principal alkaloids isolated from them (carnegine and N-methylisosalsoline)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…scoparia demonstrated strong growth inhibition of the malaria parasite in earlier study [57]. In addition, methanolic H. scoparia extract demonstrated richness in alkaloids and showed significant molluscicidal activity [56], while H. albus extract exhibited antiviral activity [54].…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…scoparia demonstrated strong growth inhibition of the malaria parasite in earlier study [57]. In addition, methanolic H. scoparia extract demonstrated richness in alkaloids and showed significant molluscicidal activity [56], while H. albus extract exhibited antiviral activity [54].…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…Galba truncatula ( G. truncatula ) has been identified as the main intermediate host of fasciolosis in southern Tunisia (Ayadi et al , 1997, Hammami & Ayadi, 1999; Hammami et al , 2007). Previous studies in our laboratories have shown the high molluscicidal activity of alkaloids especially the N-methylisosalsoline isolated from Hammada scoparia , Chenopodiaceae (Jarraya et al , 2009). It was also reported in earlier studies that crude water extracts of Solanum nigrum var.…”
mentioning
confidence: 94%
“…This species is used in traditional medicine to treat eye disorders [12,13] and to reduce scars [14], for its larvicidal activities [15,16], anticancer, antiplasmodial [17,18], anti molluscicide [19], and antileukemic [20]. However, relatively there are not many researches that have been published on his phytochemistry.…”
Section: Introductionmentioning
confidence: 99%